Forecasting the energy consumption of sectors under different NGFS scenarios and analyzing the effects on Türkiye's GDP - Gökçe, Utku. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2023)
Physical and transition risks of climate change will have an impact on countries’ economies and sectors. With proper planning and taking the necessary steps, these impacts can be mitigated. Therefore, academic studies and analyzes in this field are important. In this study, it is examined how T¨urkiye’s GDP will be affected by physical risks and transition risks under different climate scenarios. In addition, within the scope of these scenarios, it has been forecasted how the energy consumption of the sectors in T¨urkiye will be in the future. In cases where current policies are continued or the necessary measures are not taken at the right time, the impact of climate change on T¨urkiye’s GDP will be huge. At this point, it is of great importance to limit GHG emissions and not to increase the global average temperatures compared to the preindustrial revolution. Because the increase in the number of extreme weather events or the occurrence of irreversible physical events such as sea level rise can seriously affect the economies. The steps in transitioning to a low carbon economy and combating the effects of climate change will also be a huge burden for the economies. In this context, the use of renewable energy sources should be increased in Turkey and practices that can reduce emissions such as carbon tax should be introduced. In energy production, fossil fuel consumption should be reduced and alternative energy types should be used. It can be said that the Oil and Gas, Transportation and Automotive sectors will be more affected by this situation. In these sector renewable energy types may need to be used more in energy production.
Keywords: Climate change mitigation -- Turkey.; Energy consumption -- Turkey.; Energy policy -- Turkey.